Through the lens of inequality: what can we learn from CGIAR as a case study of research on the climate–security nexus? - DuttaGupta, Tanaya; Silveiracarneiro, Bia; Schapendonk, Frans; Pacillo, Grazia; Ma, Suza; Läderach, Peter R.D. (Liverpool University Press, 2023)
Whether it is climate, conflict, or COVID-19, inequality is a key component of any crisis as it can reveal why some people and regions are disproportionately impacted over others. While climate impacts interacting with inequalities can exacerbate existing drivers of insecurity, it can also leave room for institutions and interventions to foster cooperation and build resilience and peace. Focusing on insights from literature on the climate–security–inequality nexus and using CGIAR as a case study on how research for development work has engaged with the nexus, the article conducts a knowledge mapping exercise to highlight gaps and scope in mapping inequality in relation to CGIAR’s work on climate, resilience, insecurity and conflict. Key findings emerging from the analysis support that while inequality has typically been studied in relation to either climate or conflict, there is greater scope for focusing on context-specific mechanisms and pathways. The article concludes with recommendations for a growing climate-security community of practice to see and act through the lens of inequality.